NGC 7457: evidence for merger-driven cylindrical rotation in disc galaxies. Issue 1 (28th June 2019) - Molaeinezhad, A; Zhu, L; Falcón-Barroso, J; van de Ven, G; Méndez-Abreu, J; Balcells, M; Aguerri, J A L; Vazdekis, A; Khosroshahi, H G; Peletier, R F
ABSTRACT: We construct Schwarzschild orbit-based models of NGC 7457, known as a peculiar low-mass lenticular galaxy. Our best-fitting model successfully retrieves most of the unusual kinematics behaviours of this galaxy, in which, the orbital distribution of stars is dominated by warm and hot orbits. The reconstructed surface brightness of the hot component matches fairly well the photometric bulge and the reconstructed LOSVD map of this component shows clear rotation around the major photometric axis of the galaxy. In the absence of a dominant cold component, the outer part of our model is dominated by warm orbits, representing an exponential thick disc. Our orbital analysis also confirms the existence of a counter-rotating orbital substructure in the very centre, reported in previous observational studies. By comparing our model with a variety of simulation studies, and considering the stellar kinematics and populations properties of this galaxy, we suggest that the thick disc is most likely a dynamically heated structure, formed through the interactions and accretion of satellite(s) with near-polar initial inclination. We also suggest a merger-driven process as the most plausible scenario to explain the observed and dynamically modelled properties of the bulge of NGC 7457. We conclude that both the high level of cylindrical rotation and unusually low velocity dispersion reported for the NGC 7457 have most likely external origins. Therefore, NGC 7457 could be considered as a candidate for merger-driven cylindrical rotation in the absence of a strong bar in disc galaxies.